Effects of a 6-Week Agility Training Program on Emotional Intelligence and Attention Levels in Adolescent Tennis Players - Walid Selmi; Achraf Hammami; Raouf Hammami; Halil İbrahim Ceylan; Ryland Morgans; Jozef Simenko (Applied Sciences, 2024)
Tennis can be a mentally challenging sport, and emotional intelligence (EI) contributes significantly to an athlete’s psychological well-being. Thus, this study investigated the effects of 6 weeks of a combined Change of Direction (CoD) and reactive agility (RA) intervention program on emotional intelligence (EI) in pubertal tennis players. A total of 28 youth tennis players, aged 11 to 14 years, were randomly assigned to an experimental group (EXP-G, n = 15, 13 boys [age = 13.34 ± 0.98 years, maturity offset (MO) = −0.19 ± 0.96], and 2 girls [age = 12.77 ± 0.23 years, MO = 0.78 ± 0.04]) or a control group (CON-G, n = 13, 8 boys [age = 13.37 ± 0.75 years, MO = 0.00 ± 0.71], and 5 girls [age = 13.50 ± 0.92 years, MO = 1.41 ± 1.07]). The EXP-G performed combined CoD and RA training across the 6-week intervention period. The CON-G continued with the normal five 20 min regular tennis-specific training sessions per week, including technical and tactical drills and a small-sided games format. The overall training volume was similar between groups. Pre- and post-training, Profile of Emotional Competence (PEC, [EC TOTAL: global score of emotional competence level; EC INTRA: score of intra-personal emotional competence; EC INTER: score of inter-personal emotional competence]) and d2 attention tests were assessed. The present study employed an Analysis of Covariance (ANCOVA) with pre-test covariance to assess between-group differences (EXP-G vs. CON-G) at the post-test phase, utilizing baseline values as covariates. Noteworthy outcomes were observed, indicating statistically significant and substantial between-group disparities at post-test for various measures. Specifically, these differences were evident in the attention domain (effect size, d = 1.08 [Large], p = 0.001), the EC TOTAL test (effect size, d = 0.70 [Medium], p = 0.017), the EC INTA (effect size, d = 1.35 [Large], p = 0.001), and the EC INTER (effect size, d = 0.83 [Large], p = 0.009) tests. Due to the importance of agility training for overall competitive performance in tennis, our results suggest that young players should perform such training programs as part of conditioning training if the goal is to improve emotional intelligence and mental well-being.